Effective rheology of immiscible two-phase flow in porous media consisting of random mixtures of grains having two types of wetting properties - Fyhn, Hursanay; Sinha, Santanu; Hansen, Alex (Frontiers in Physics, 2023)
We consider the effective rheology of immiscible two-phase flow in porous media consisting of random mixtures of two types of grains having different wetting properties using a dynamic pore network model under steady-state flow conditions. Two immiscible fluids, denoted by "A" and "B" flow through the pores between these two types of grains denoted by "+" and "-". Fluid "A" is fully wetting and "B" is fully non-wetting with respect to "+" grains whereas it is the opposite with "-" grains. The direction of the capillary forces in the links between two "+" grains is therefore opposite compared to the direction in the links between two "-" grains, whereas the capillary forces in the links between two opposite types of grains average to zero. For a window of grain occupation probability values, a percolating regime appears where there is a high probability of having connected paths with zero capillary forces. Due to these paths, no minimum threshold pressure is required to start a flow in this regime. While varying the pressure drop across the porous medium from low to high in this regime, the relation between the volumetric flow rate in the steady state and the pressure drop goes from being linear to a power law with exponent 2.56 to linear again with increasing pressure drop. Outside the percolation regime, there is a threshold pressure necessary to start the flow. No linear regime is observed for low pressure drops. When the pressure drop is high enough for there to be flow, we find that the flow rate depends on the excess pressure drop to a power law with exponents around 2.2-2.3. At even higher excess pressure drops, the relation becomes linear. We see no change in exponent for the intermediate regime at the percolation critical points where the zero-capillary force paths disappear. We measure the mobility at the percolation threshold at low pressure drops so that the flow rate versus pressure drop is linear. Assuming a power law, the mobility is proportional to the difference between the occupation probability and the critical occupation probability to a power of around 5.7.